The balancing act : creating healthy dependency and connection without losing yourself - Tawwab, Nedra Glover (Tarcher, an imprint of Penguin Random House, 2026)
"Every relationship in our lives - from love and close friendship to extended family and our wider social circle - is a balancing act. If we give too much, we begin to lose ourselves. If we protect ourselves too much, we lose the closeness we all need. Getting the balance right is how we find more connection, authenticity, and joy. The Balancing Act is a roadmap for finding that balance. With her signature blend of clarity and compassion, therapist Nedra Glover Tawwab sheds light on healthy dependency, and how to achieve it. Along the way, she unpacks buzzwords and trending topics including codependency, attachment styles, inner family systems, and more - offering practical advice for recognizing our needs, navigating conflict, and finding more harmony with the important people in our lives. Whether you're yearning for more trust with a spouse or partner, more clarity with a best friend or sibling, or more agency in how you show up in the world, these insights will help you reevaluate, reset, and relate better"-- Provided by publisher.